Fungsi Dewan Hak Asasi Manusia Eropa Dalam Menangani Pelanggaran Hak Asasi Manusia Di Hungaria Berdasarkan Piagam Hak Asasi Manusia Eropa - Brian Stevano Ukru; Josiana Agusthina Yvonne Wattimena; Johanis Steny Franco Peilouw (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The function of the European Human Rights Council in dealing with human rights violations against refugees and asylum seekers in Hungary and the form of accountability of the Hungarian State based on the European Human Rights Charter.Purposes of the Research: This writing aims to examine and analyze how the European Human Rights Council functions in dealing with human rights violations in Hungary based on the European Human Rights Charter.Methods of the Research: The research method in this paper uses a normative juridical research type. The research approach used is a statutory approach, a conceptual approach and a case approach. The procedure for collecting legal materials uses primary legal materials and secondary legal materials through books, articles, journals and the writings of legal experts, as well as legal materials analysis techniques in this study using qualitative analysis techniques.Results of the Research: The results obtained are to explain that the function of the European Human Rights Council is to guarantee the protection of human rights for refugees and asylum seekers. The form of responsibility of the Hungarian State under the European Charter of Human Rights.